Pengaruh Konten Instagram Dan Kredibilitas Beauty Influencer Nanda Arsyinta Terhadap Gaya Hidup Remaja - Titania, Intan Putri; Sudradjat, Ratih Hasanah (Jurnal Pustaka Komunikasi, 2024)
Researchers identified the problem in this research, namely how much influence Instagram content and the credibility of beauty influencer Nanda Arsyinta have on teenagers' lifestyles. The aim of this research is to explain how much influence Instagram content and the credibility of beauty influencer Nanda Arsyinta have on teenagers' lifestyles. Whether Instagram content and credibility are high or low will make followers trust him and follow his lifestyle. Therefore, Instagram content and Nanda Arsyinta's credibility as a beauty influencer are very interesting to research, whether there is an influence on teenagers' lifestyles or not. This research method is quantitative research with descriptive research type. In this research, researchers used non-probability sampling techniques, with a total of 400 teenagers aged 10-28 years. Based on the results of simultaneous hypothesis testing (f test) it can be concluded that H0 is rejected and H1 is accepted, because , it can be concluded that there is a significant influence of Instagram content and the credibility of beauty influencer Nanda Arsyinta on teenage lifestyles.